Research on Profitability Strategies of Online Audio Platforms in the Context of AI-Enabled Era - Case study of the Ximalaya - Li, Linjing (Transactions on Economics, Business and Management Research, 2024)
The AIGC model has been widely used in the content production industry in recent years. Chinese online audio market is heavily influenced by the development of AI technology. At the same time, in the past decade, many Chinese online audio platforms have been facing the problem of high content costs and difficulty in achieving profitability. Therefore, it is of great significance to study the profit model of online audio platforms. This study analyses Ximalaya's profitability strategy in the context of the AI-enabled era. It is based on a literature review, case studies and data analysis. Besides, Ximalaya's business logic, profit model and profit strategy are comprehensively analyzed in this study. This study finds that Chinese online audio platforms, represented by Ximalaya, already have relatively complete profit strategies and industrial chains. However, the use of AI in online audio platforms is still in the very early stages of development. Online audio platforms are increasingly utilizing AI technology to improve platform operations, resulting in cost savings and increased efficiency.